High frequency CCR5 editing in human hematopoietic stem progenitor cells protects xenograft mice from HIV infection - Daniel T. Claiborne; Zachary Detwiler; Steffen S. Docken; Todd D. Borland; Deborah Cromer; Amanda Simkhovich; Youdiil Ophinni; Ken Okawa; Timothy Bateson; Tao Chen; Wesley Hudson; Radiana Trifonova; et al. (Nature Communications)
Abstract The only cure of HIV has been achieved in a small number of people who received a hematopoietic stem cell transplant (HSCT) comprising allogeneic cells carrying a rare, naturally occurring, homozygous deletion in the CCR5 gene. The rarity of the mutation and the significant morbidity and mortality of such allogeneic transplants precludes widespread adoption of this HIV cure. Here, we show the application of CRISPR/Cas9 to achieve >90% CCR5 editing in human, mobilized hematopoietic stem progenitor cells (HSPC), resulting in a transplant that undergoes normal hematopoiesis, produces CCR5 null T cells, and renders xenograft mice refractory to HIV infection. Titration studies transplanting decreasing frequencies of CCR5 edited HSPCs demonstrate that <90% CCR5 editing confers decreasing protective benefit that becomes negligible between 54% and 26%. Our study demonstrates the feasibility of using CRISPR/Cas9/RNP to produce an HSPC transplant with high frequency CCR5 editing that is refractory to HIV replication. These results raise the potential of using CRISPR/Cas9 to produce a curative autologous HSCT and bring us closer to the development of a cure for HIV infection.